Development of Digital Identification Instruments for Mentally Retarded Children - Rejeki, Dewi Sri; Sari, Erma Kumala; Salim, Abdul; Subagya, Subagya (Department of Special Education, 2019)
This study aims to develop a digital identification instrument-based Decision Support System (DSS) for mentally disabled children. First-year research consisted of three stages, namely (a) instrument need analysis, (b) instrument prototype development, (c) instrument validation. The study involved 20 special schools taken by purposive sampling from eight districts/cities in Central Java. The method of collecting data at the needs analysis stage uses a questionnaire given to 32 respondents (teachers and principals). At the stage of prototype development, data collection is done by using a web-based DSS development technique. Furthermore, the instrument validation stage is done through professional judgment with Focus Group Discussion (FGD) techniques involving special education experts, information and technology experts, psychometric experts, language experts, psychologists, and users/teachers. Data analysis was performed with quantitative descriptive and qualitative descriptive techniques. The results of the study at the needs analysis stage showed that 75% of respondents had difficulty in compiling identification instruments for mentally disabled children; all respondents (100%) needed the development of identification instruments for mentally disabled children, and 50% of respondents chose identification instruments in digital form. At the instrument development stage, mentally disabled children's characteristics based on the previous DSM-V criteria are described in the indicators. This digital instrument's identification results are still limited to indications, so that it needs to be continued with more in-depth assessment by authorized professionals. Expert validation results at the instrument validation stage indicate that this digital identification instrument for mentally disabled children meets the eligibility criteria with improvements in language, web appearance, and the instrument's technical operation. Furthermore, the instrument prototype is repaired and will be continued with small-scale and wide-scale trials.